Analisis Yuridis Lelang Penjualan Barang Jaminan Akibat Debitur Wanprestasi dalam Perjanjian Kredit - Sri Suryada Br. Sitorus (Inovasi Pratama Internasional. Ltd, 2022)
The existence of the imposition of Mortgage on banks can be a security for bank credit. The formulation of the problem in this journal is how the legal arrangements for credit agreements with mortgage guarantees are carried out, how is the execution of the auction of collateral or collateral in the credit agreement, how are legal considerations by judges in the execution of the debtor's credit collateral auction in the Decision of the Supreme Court of the Republic of Indonesia Number 1316 K/Pdt /2018. This study uses a descriptive method through a normative approach (legal research) to obtain secondary data. The collected data will be analyzed carefully using qualitative analysis or described in sentences. Legal protection for land certificate holders in the promises contained in the Deed of Granting Mortgage as referred to in Article 11 paragraph (2) UUHT. Regarding guarantees, Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles stipulates that property rights, cultivation rights, and building use rights can be used as debt guarantees with encumbrances of Mortgage Rights. For the execution of the debtor's default settlement through execution, among others: 1. Execution through underhand sales 2. Parate execution, 3. Execution based on executorial title. The legal consideration by the judge in the execution of the auction of credit collateral belonging to the debtor in the Decision of the Supreme Court of the Republic of Indonesia Number 1316 K/Pdt/2018 is that the plaintiff as the Debtor has a credit debt to Defendant I/Bank Danamon (Creditor) by submitting collateral for the Certificate of Ownership Number 3088 on behalf of the Plaintiff and as a result of the debtor defaulting so that in order to pay off the debtor's debt, the creditor can take from the proceeds of the auction sale of the collateral goods submitted by the plaintiff as the debtor based on the power of attorney to sell the auction from the plaintiff.